Cardiac effects of prolonged endurance exercise in young and older athletes - Frandsen, J.; Aaroe, M.; Sehestedt, T.; Sahl, R. E.; Hansen, M. T.; Lie-Olesen, M. M.; Nielsen, A. B.; Rømer, T.; Ingersen, A.; Larsen, S.; Dela, F.; Sacchetti, M.; et al. (Scandinavian Journal of Medicine & Science in Sports, 2025)
To evaluate the effects of prolonged endurance exercise on the thin-walled chambers of the right ventricle (RV) and left atrium (LA), and heart rate (HR) in young (YA) and older (OA) athletes. Seven YA and seven OA (30 ± 5 and 65 ± 6 years; VO2max: 61.5 ± 2.2 and 46.8 ± 4.1 mL/min/kg, respectively) were studied before, during, and after a 15-day cycling journey from Copenhagen (CPH) to Palermo (PMO) (~3000 km). Transthoracic echocardiography (TTE) was performed in both groups, and additional stress echocardiography (SE) in OA. Speckle-tracking echocardiography was applied for RV free-wall strain, LA global peak-atrial longitudinal strain (PALS), and contraction strain (PACS). Assessments were made at baseline (CPH), at arrival (PMO), and for OA six months post-intervention (CPH+6). RV size and function were similar between YA and OA at baseline and remained unchanged at rest post-intervention. In OA, SE revealed decreased RV function during exercise at PMO, normalizing at CPH+6. LA size remained unchanged, but OA showed higher baseline filling pressure (E/e'), PACS, and LA stiffness index with lower PALS than YA. Post-intervention, PALS decreased (p < 0.01) while E/e', PACS, and LA stiffness index remained stable. Resting HR increased in OA (p = 0.002) but not in YA. VO2max was higher in YA and decreased in OA post-intervention (p = 0.056). Although RV size and resting function were unaffected, RV exercise-induced dysfunction was observed in OA, potentially due to increased LA stiffness. These findings suggest age-related cardiac fatigue and extended recovery time in OA.